Knowledge, attitude, and perceptions of the public toward the COVID-19 vaccine: A cross-sectional study from India - Sameer Dhingra, Arun Chandramohan, Rajasree Udayakumary, Doddolla Lingamaiah, Krishna Murti, Sanjiv Singh, Katia Iskander (Journal of Applied Pharmaceutical Science, 2023)
This cross-sectional study was based on an e-survey conducted among 507 individuals to assess the knowledge, attitude, and perceptions (KAP) of the public toward the COVID-19 vaccine. The survey was carried out by employing a questionnaire comprising four sections which included demography, KAP toward the COVID-19 vaccine. Bivariate group variance analysis and multivariable regression were used to evaluate the knowledge and perceptions about the COVID-19 vaccine. The mean score of the knowledge out of 5 was 3.34 ± 1.95 and of perception out of 10 was 7.36 ± 2.48. Seventy-one percent of the participants believed that the vaccines have side effects and most of the participants (52.56%) stated that healthcare workers should be vaccinated first. The results obtained from the study indicate that the people’s understanding and attitudes toward the COVID-19 vaccinations are good, but there are certain groups of the population that have poor knowledge and perception, such as low socioeconomic status and lack of education. Certain educational awareness programs can be made to improve their KAP toward the COVID-19 vaccination and to encourage them to administer the vaccines.
Keywords: COVID-19 vaccine, knowledge, attitude, perception, vaccination